Assessing the feasibility of CRISPRa approaches to enhance protein-based biomaterial expression in bacterial systems for more efficient production - Pablo Rodríguez-Alonso; Viktoriya Chaskovska; Desiré Venegas-Bustos; Alba Herraiz; Matilde Alonso; Jose Carlos Rodríguez-Cabello (Materials Today Bio)
Recombinant protein production is crucial for biomedical and industrial applications; however, achieving high yields for complex protein-like biomaterials such as elastin-like recombinamers (ELRs) remains challenging. ELRs, protein-based polymers derived from tropoelastin, emulate the mechanical and bioactive properties of natural tissues, making them valuable for numerous uses. Despite their promise, implementing a sophisticated molecular system for ELR production in Escherichia coli involves overcoming multiple hurdles, including metabolic bottlenecks and low yields. In this study, we employed a CRISPR activation (CRISPRa) system to enhance ELR expression in E. coli. Although further optimization is required to reach industrial-scale outputs, our findings establish a proof of concept for taking advantage of CRISPRa to boost recombinamers yields. Such improvements represent a crucial step toward scalable production, facilitating the commercial adoption of ELRs and, in general, recombinamers not only in biomedical applications but also in broader industries that stand to benefit from these versatile biomaterials.